Peran Budaya Organisasi dalam Membentuk Perilaku dan Kinerja Pegawai - Nugraha, Risman; Haris Muchtar, Abdul (Observasi : Jurnal Publikasi Ilmu Psikologi, 2025)
Organizational culture plays a crucial role in shaping employee behavior and performance. A strong organizational culture fosters a conducive work environment, enhances employee engagement, and motivates them to achieve optimal performance. This study aims to analyze how organizational culture influences employee behavior and performance while identifying the key cultural elements that significantly impact productivity. This research employs a literature review method, examining recent scholarly works on organizational culture, employee behavior, and performance. The findings indicate that a positive organizational culture—characterized by open communication, alignment of values with company goals, and managerial support—directly enhances work motivation, job satisfaction, and employee productivity. Conversely, a weak organizational culture can lead to dissatisfaction, high turnover rates, and decreased productivity. The implications of this study highlight the importance of fostering a strong and adaptive work culture to sustain and improve employee performance. Additionally, this study offers strategic recommendations for managers and organizational leaders in developing a culture that promotes innovation, collaboration, and employee well-being.